Geochemical and sedimentological data of the JPC42 sediment core from Wide Channel, Chile - Matthias Troch; Sebastien Bertrand; Julia S Wellner; Carina Beatriz Lange; Konrad A Hughen (PANGAEA, 2023)
Organic geochemical and sedimentological data analyzed at a 10 to 20 cm interval on the JPC42 and KC41 cores including total organic carbon content, stable carbon isotopes, marine organic carbon content, calcium carbonate, grain-size mode, and ice-rafted debris (particles >150 μm).
In: Troch, M et al. (2023): Geochemical and sedimentological analysis of the 12.2 m long, radiocarbon-dated JPC42 sediment core from Wide Channel (50°S; Chile) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.950429